2019
DOI: 10.1021/acs.jmedchem.9b01562
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of Potent Pan-Genotypic HCV NS5A Inhibitors Containing Novel Tricyclic Central Core Leading to Clinical Candidate

Abstract: The identification of a novel class of potent pan-genotypic NS5A inhibitors with good pharmacokinetic profile suitable for potential use in treating HCV infections is disclosed here. The present series of compounds are with less complex tricyclic central core, identified through a systematic SAR study carried out on biphenyl moiety. The SAR outcome has confirmed the requirement of near planar and linear conformation of the molecule to achieve the best pan-genotypic activity. In addition, SAR with substituted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, a study performed by Ramdas et al aimed at introducing a lipophilic spirocyclic scaffold in the linker region between the peptidoid parts showed that the spirocyclic linker 226 displayed subnanomolar activity, though only toward the hepatitis C virus genotype 1b (GT1b) replicon. 151 The fully planar tricyclic linker was obviously more suitable, leading to lead compound 227, which exhibited picomolar activity toward both replicons GT1a and GT1b (Figure 26). The work of Yang et al demonstrated that starting with a promising spirocyclic scaffold may not guarantee ending with a spirocyclic inhibitor.…”
Section: Replacement Of Spirocyclic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study performed by Ramdas et al aimed at introducing a lipophilic spirocyclic scaffold in the linker region between the peptidoid parts showed that the spirocyclic linker 226 displayed subnanomolar activity, though only toward the hepatitis C virus genotype 1b (GT1b) replicon. 151 The fully planar tricyclic linker was obviously more suitable, leading to lead compound 227, which exhibited picomolar activity toward both replicons GT1a and GT1b (Figure 26). The work of Yang et al demonstrated that starting with a promising spirocyclic scaffold may not guarantee ending with a spirocyclic inhibitor.…”
Section: Replacement Of Spirocyclic Scaffoldsmentioning
confidence: 99%
“…In the introductory section, we mentioned 14 , an NS5A inhibitor that exhibits a spirocyclic proline analogue. However, a study performed by Ramdas et al aimed at introducing a lipophilic spirocyclic scaffold in the linker region between the peptidoid parts showed that the spirocyclic linker 226 displayed subnanomolar activity, though only toward the hepatitis C virus genotype 1b (GT1b) replicon . The fully planar tricyclic linker was obviously more suitable, leading to lead compound 227 , which exhibited picomolar activity toward both replicons GT1a and GT1b (Figure ).…”
Section: Spirocycles Back and Forth: Bioisosteric Replacement Of Spir...mentioning
confidence: 99%
“…Drug discovery efforts are actively ongoing to discover new pan-genotypic inhibitors of NS5A that are expected to decrease the incidence of treatment failure associated with low barrier to resistance of most marketed NS5A inhibitors for genotype 1 subtype a (GT1a) 196 , 197 , 198 as well as improve the pharmacokinetic profiles of existing drugs by prodrug synthesis to enhance solubility properties and simplify drug dosage formulations (e.g., pibrentasvir). 199 …”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Recent studies have described new NS5B nucleotide analogues, including guanosine [74] and uridine analogues [75], and non-nucleoside inhibitors [76,77]. New pan-genotypic NS5A inhibitors have been also described [78][79][80]. The aim in developing new DAAs is to obtain compounds with a broader capacity to inhibit the different genotypes and HCV variants, and having a better metabolic profile [81].…”
Section: Hcv Therapymentioning
confidence: 99%